2022
DOI: 10.1021/acs.jpclett.2c00232
|View full text |Cite
|
Sign up to set email alerts
|

Role of Molecular Layering in the Enhanced Mechanical Properties of Stable Glasses

Abstract: The density, degree of molecular orientation, and molecular layering of vapor-deposited stable glasses (SGs) vary with substrate temperature (T dep ) below the glass-transition temperature (T g ). Density and orientation have been suggested to be factors influencing the mechanical properties of SGs. We perform nanoindentation on two molecules which differ by only a single substituent, allowing one molecule to adopt an in-plane orientation at low T dep . The reduced elastic modulus and hardness of both molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
(138 reference statements)
1
7
0
Order By: Relevance
“…Physical vapor deposition (PVD) can prepare glassy films with a range of characteristics depending upon deposition conditions. ,, In particular, PVD can produce ultrastable and also high density glasses. ,, Previous studies on vapor-deposited glasses have shown high kinetic stability, ,,, low enthalpy, ,,, high mechanical moduli, high chemical stability and high photostability . These properties can be explained by the surface equilibration mechanism, which is based on high molecular mobility at the free surface relative to the bulk. ,,, Consistent with this mechanism, the density of a vapor-deposited low molecular weight system, ethylbenzene, was shown to approach the density of the ideal glass .…”
mentioning
confidence: 94%
“…Physical vapor deposition (PVD) can prepare glassy films with a range of characteristics depending upon deposition conditions. ,, In particular, PVD can produce ultrastable and also high density glasses. ,, Previous studies on vapor-deposited glasses have shown high kinetic stability, ,,, low enthalpy, ,,, high mechanical moduli, high chemical stability and high photostability . These properties can be explained by the surface equilibration mechanism, which is based on high molecular mobility at the free surface relative to the bulk. ,,, Consistent with this mechanism, the density of a vapor-deposited low molecular weight system, ethylbenzene, was shown to approach the density of the ideal glass .…”
mentioning
confidence: 94%
“…Physical vapor deposition (PVD) is a well-established technique to prepare glassy thin films of a wide array of materials including small organic molecules, chalcogenides, , metallic glasses, , and polymers. Glasses produced via PVD can have remarkable properties that cannot be achieved using other preparation techniques, including reduced enthalpy, , increased density, , multiple amorphous structures, suppressed secondary relaxations, and anisotropic molecular orientation. , In addition, PVD glasses can exhibit high kinetic stability, which is the tendency to resist devitrification upon heating a glass above its glass transition temperature, T g . Significant progress has been made to understand how deposition conditions and molecular shape , control the structure and properties of the resulting glass.…”
Section: Introductionmentioning
confidence: 99%
“…A signi cant linear coe cient on the speci c heat at the lowest temperatures, ascribed to the "universal" presence of TLS in glasses, was found to persist invariant in geologically hyperaged glasses of amber (a typical polymer glass) [30−32], when comparing the pristine samples (up to 110 My aged) to the rejuvenated samples. One possible difference to take into account between standard glasses and PVD glasses is that the former are essentially homogeneous and isotropic, whereas the latter typically exhibit anisotropic packing and layered structures [33][34][35][36] that can play a role in different properties [37][38][39][40][41][42]. In fact, the anisotropy of IMC ultrastable glasses was argued in Ref.…”
Section: Introductionmentioning
confidence: 99%